DESEMPENHO ZOOTÉCNICO DE SUÍNOS EM CAMA SOBREPOSTA DE GIRASSOL - Cappellari, Geverson J.; Garcia, Dagmar C.; Fernandes, Patrick J.; Silva, Jose A. G. d.; Quadros, Valmir J. d.; Carbonera, Roberto; Fernandes, Sandra B. V.; Berto, Jorge L.; Uhde, Leonir T.; Maixner, Adriano R. (Salão do Conhecimento, 2013)
Resumo